What drives investor response to CSR performance reports? - Guiral, Andres (2022)
Recent research finds that investors' assessments of a stock's fundamental value are influenced by corporate social responsibility (CSR) performance through the affect-as-information heuristic. We extend prior research by examining two boundary conditions for the use of this heuristic: (i) whether the CSR performance relates to activities that are integrated in a firm's core business practices (material CSR issues) or not (immaterial CSR issues), and (ii) whether the CSR performance is positive or negative. Employing an experimental method, we find that the affect-as-information heuristic applies only to immaterial CSR issues but not to material CSR issues, and only to positive but not negative CSR performance. Our findings suggest that investors likely use a heuristic approach to process immaterial and positive CSR issues, and a more deliberate and systematic approach to process material or negative CSR issues. Our study has both practical and theoretical implications.